Barbara McClintock : Nobel Prize geneticist - Fine, Edith Hope. (Springfield, NJ : Enslow Publishers, 1998)
Presents the life and career of the geneticist who spent many years studying the cells of maize and in 1983 was awarded the Nobel Prize in Physiology or Medicine.
Includes bibliographical references (p. 125) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
2.5.
2.5
Keywords: McClintock, Barbara, -- 1902- -- Juvenile literature; McClintock, Barbara, -- 1902-; McClintock, Barbara, -- 1902-; Corn -- Genetics; Women geneticists -- United States -- Biography -- Juvenile literature; Geneticists; Nobel Prizes -- Biography; Women geneticists; Women -- Biography; Geneticists -- Biography; Nobel Prizes -- Biography; Women geneticists -- Biography; Women -- Biography